The Impact of Using heat Insulation in Reducing Operational Energy and LCA Emission in Local Building, - Younis Mahmood M. Saleem; Mohammad Salman Dawood (Iraqi Journal of Architecture and Planning, 2017)
The Building sector is one of the biggest sector in energy consumption and greenhouse gases emission, and the biggest phase of building life cycle that responsible of that consumption of energy and emission is operation phase (specially Heating and cooling) and itâ€™s effected directly by building material thermal conductivity. There is a different ways to reduce operation consumption of energy and life cycle emission like using insulated wall and glazing. So the research problem will be â€œthe need of applied research that compare the energy consumption of energy and emissions change in masonry building when using different thermal performance skinsâ€. So the goal of the research is â€œmeasure and compare Building energy consumption in operation phase and emissions in life cycle of Masonry Buildingâ€. The conclusion of this research is that the possibility to reduce energy used in building to 44.8% and reducing emission to 56.4% using cavity wall and insulation in Masonry Building. Assessed by Life Cycle Assessment method. Key Words: Emissions, Life Cycle Assessment (LCA), Project Management â€“ Environmental Management.